(untitled) (Вестник транспорта - Transport xabarnomasi, 2026)
The article analyzes the importance of a condition-based approach to improving the efficiency of the technical maintenance (TM) system for aircraft. Methods for optimizing TM processes through operational data analysis, failure forecasting, and the effective organization of preventive measures are examined. Issues related to the differences between preventive and reactive maintenance and the application of modern diagnostic technologies are highlighted. The approaches presented in the article help enhance flight safety and reduce maintenance costs.